Pengaruh Transformasi Digital terhadap Kualitas Pelayanan Administrasi dalam Perspektif Manajemen Pendidikan Islam (Studi SMA Al Hidayah Sinar Harapan Kabupaten Lampung Utara) - Tri ahsani taqwim; Indra Wahyudi; Nara Purnama Wari (JURNAL MAPPESONA, 2026)
This study aims to analyze the level of digital transformation, evaluate the quality of administrative services, and examine the effect of digital transformation on the quality of administrative services from the perspective of Islamic education management at SMA Al Hidayah Sinar Harapan, North Lampung Regency. This research employs a quantitative approach with a causal research design. Data were collected through questionnaires distributed to 30 respondents using a simple random sampling technique. Data analysis was conducted using SPSS, including validity testing, reliability testing, classical assumption tests, and simple linear regression analysis. The results indicate that all items for both the digital transformation and service quality variables are valid (r-count > 0.361) and reliable, with Cronbach’s Alpha values of 0.872 and 0.889, respectively. The regression analysis shows that digital transformation has a positive and significant effect on the quality of administrative services, with a regression coefficient of 0.765, a t-value of 7.372, and a significance level of 0.000 < 0.05. The coefficient of determination (R Square) of 0.659 indicates that 65.9% of the variation in administrative service quality is explained by digital transformation. Therefore, digital transformation plays a crucial role in improving the quality of administrative services within the framework of Islamic education management.